Literature Study Relationship Between Physical Condition of The House and Occupancy Density With The Incidence of ISPA Disease In Toddlers - Wahyuni, Marjan; Hardianti, Siti; Sartika, Retno Dewi (Universitas Muhammadiyah Kalimantan Timur, 2023)
Acute Respiratory Tract Infection can be defined as a respiratory tract disease caused by infectious agents that can be transmitted from human to human. The infectious agents in question are viruses, bacteria, and other factors such as the environment and the host. Acute Respiratory Tract Infection is influenced or caused by three things, namely the presence of germs, the state of endurance, the state of the environment, and air quality. The design of this research is Literature Review or literature review. Literature review study is a method used to reveal data and sources related to a particular topic that can be obtained from various journal sources, and data from the Samarinda City Health Office which are accessed online.